2010
DOI: 10.1590/s1413-81232010000800011
|View full text |Cite
|
Sign up to set email alerts
|

Bullying in Brazilian schools: results from the National School-based Health Survey (PeNSE), 2009

Abstract: The aim of this study is to identify and describe the occurrence of bullying among students in the 9th year (8th grade) from public and private schools from 26 Brazilian state capitals and the Federal District. It is a cross-sectional study involving 60,973 students and 1,453 public and private schools. Data analysis indicates that 5.4% (IC95%: 5.1%-5.7%) of students reported having suffered bullying almost always or always in the last 30 days, 25.4% (IC95%: 24.8%-26.0%) were rarely or sometimes the victim of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0
14

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 15 publications
3
30
0
14
Order By: Relevance
“…Although some items could be further modified to include only two response categories, the three alternatives were maintained for all items to ensure uniformity between the bully and victim scales. The presence of multiple categories allows for an estimation of behavior frequency, which is especially important since repetition is a core feature of bullying (Malta et al, 2010). Thus, use of the IRT model confirmed that the behaviors measured by the scale are expressions of the underlying construct, and also allowed us to determine the performance of each item of the QBO construct for Brazilian adolescents (Andrade et al, 2000;Pasquali, & Primi, 2003).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Although some items could be further modified to include only two response categories, the three alternatives were maintained for all items to ensure uniformity between the bully and victim scales. The presence of multiple categories allows for an estimation of behavior frequency, which is especially important since repetition is a core feature of bullying (Malta et al, 2010). Thus, use of the IRT model confirmed that the behaviors measured by the scale are expressions of the underlying construct, and also allowed us to determine the performance of each item of the QBO construct for Brazilian adolescents (Andrade et al, 2000;Pasquali, & Primi, 2003).…”
Section: Discussionmentioning
confidence: 80%
“…Recurrence over time is also a key aspect of bullying (Berger, 2007), along with the involvement of a bully, or perpetrator, and of a victim, the target of the aggression. Some individuals may be at the same time perpetrators and victims, and are therefore classified as bully-victims (Malta et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different results were obtained in a study involving more than 60,000 students of public and private schools in the 26 Brazilian State capitals and the Federal District [30], which found 5.40% of bullying victims. Being a victim of bullying was not associated with overweight; however, in the bivariate analysis, the victims of bullying were 78% more likely (PR=1.78) to show ED symptoms than those who were not bullying victims.…”
Section: Discussionmentioning
confidence: 83%
“…Finalmente, destacam-se os dados referentes à presença de álcool e, sobretudo, armas brancas e de fogo nas escolas. O combate à entrada de drogas e armas nas escolas é de vital importân-cia, uma vez que se compreende que sua presença se constitui como potencial causadora e/ou agravante das situações de violência 20 . Diante desse quadro preocupante de violência escolar, se faz necessário refletir acerca de algumas possibilidades de proteção aos jovens e enfrentamento ao fenômeno.…”
Section: Discussionunclassified